Hybrid particleboard properties from acacia mangium and 'petal relalang' (leucaena leucocephala) using urea-formaldehyde resin / Mohamad Syazwan Saleh - Saleh, Mohamad Syazwan (Faculty of Applied Sciences, 2015)
Hybrid particleboard properties from acacia mangium and 'petal belalang' (leucaena leucocephala) using urea-formaldehyde resin. The main objective of this study was to evaluate the potential of fast growing species, Acacia Mangium and 'Petai Belalang' (Leucaena leucocephala) as alternative to supplement the rubberwood in manufactured of particleboard. The focus was on particleboard which produced from different resin content (8%, 10% and 12%) and ratio of species Acacia (100%), Acacia + Petai Belalang (30% + 70%), Acacia + Petai Belalang (50% + 50%), Acacia + Petai Belalang (70% + 30%), and Petai Belalang (100%) The particleboards were tested for their mechanical and physical properties based on Japanese Industrial Standard (JIS A 5908 : 2003) requirement. Wood ratio of species had significant effects on MOR, MOE, IB, TS and WA On other hand, resin content showed significant effect on TS and WA From the study it was revealed that 100% or homogeneous board from Acacia species and with resin content of 12% had the highest value for MOR (1712MPa), MOE (2127MPa), and the best TS (1323%) and WA (6437%) value.